The effects of body dysmorphic disorder on women's quality of life and body image at difference stages of pregnancy - A. Hope Gibson; Yuliana Zaikman; Rose Rodriguez; Brook Bennett (BMC, 2024)
Abstract Background Pregnancy is a time of great change for women, both mentally and physically. For any pregnant woman, this time of change can be difficult as the woman needs to constantly adapt to the rapidly changing body. This change could be especially challenging for a woman who has previously struggled with symptoms of body dysmorphic disorder (BDD), which cause individuals to perceive part(s) of their body as particularly ugly or deformed, creating distress that affects several areas of functioning. These distorted perceptions have been associated with low self-reported functioning in physical and psychological areas. The present study assessed the effects of BDD symptoms on the physical and psychological functioning of pregnant women at different points throughout their pregnancy. Methods During July 2021 through April 2022, one hundred and fifty-eight women were recruited from various mothers' Facebook groups, women's centers across a city in Southern Texas, and through Prolific. The sample consisted of women in their first, second and third trimesters, as well as women three months postpartum. Information about the presence of BDD symptoms, quality of life, and body image was collected. Results We found that women in their second trimester possess the highest quality of life compared to women in their first trimester, third trimester or postpartum. Women with high BDD symptoms have lower quality of life and lower body image compared to women with low BDD, especially for those in their first or third trimesters. Conclusions These findings illustrate the necessity of targeted interventions and support for pregnant women, especially those with BDD symptoms, in order to promote their well-being throughout pregnancy and postpartum.